Alkali Activation of Mortars Containing Different Replacement Levels of Ground Granulated Blast Furnace Slag - Bilim, Cahit; Atis, Cengiz Duran; Ati, Cengiz Duran (Elsevier Sci Ltd, 2012)
The aim of the present study is to investigate some properties of alkali-activated mortars containing slag at different replacement levels. Ground granulated blast furnace slag was used at 0%, 20%, 40%, 60%, 80% and 100% replacement by weight of cement, and liquid sodium silicate having three different Na dosages was chosen as the alkaline activator. In this research, carbonation resistance measurements and compressive and flexural strength tests were performed on the mortar specimens with size of 40 x 40 x 160 mm. The findings obtained from the tests showed that carbonation depth values of the mortars decreased with the increase of activator dosage. Additionally, compressive and flexural strength values increased with the increase in activator concentration and slag replacement level. Portland cement/slag mortars activated by liquid sodium silicate exhibited lower strength than the slag alone activated by the same activator. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Alkali-Activated Mortars; Ground Granulated Blast Furnace Slag; Liquid Sodium Silicate; Mechanical Properties; Carbonation